PENGARUH KOMPETENSI GURU TERHADAP KARAKTER PESERTA DIDIK (SURVEI DI SMK JAKARTA PUSAT 1) - Zahra Eka Sawitri; Suprapto; Kurnia Illahi; Arifah Nur Rahmah; Nadiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is grounded in the importance of teacher competence in the educational process, particularly in shaping and developing students' character. Teachers do not merely convey knowledge but also play an essential role in modeling, guiding, directing, and forming students' attitudes and behavior. This study aimed to measure the extent of the influence of teacher competence on students' character at SMK Jakarta Pusat 1. A quantitative approach with a descriptive analytic correlational method was used. The sample consisted of 76 students selected through simple random sampling from a population of 756 students. Data were collected through questionnaires, observation, documentation, and interviews, and were analyzed using Pearson Product Moment correlation and simple linear regression. The results showed a positive and significant relationship between teacher competence and students' character, with a correlation coefficient (rxy) of 0.423 and a significance value of 0.000 (< 0.05). The coefficient of determination (R Square) was 0.179, indicating that teacher competence contributed 17.9% to variations in students' character, while the remaining 82.1% was influenced by other factors outside this study. Hypothesis testing showed that ro (0.423) exceeded rt at both the 5% (0.227) and 1% (0.296) significance levels, so the alternative hypothesis (Ha) was accepted. Therefore, strengthening teacher competence in the pedagogical, personal, social, and professional domains can support the optimal development of students' character. Keywords: Teacher Competence, Student Character